Seqüência de moebius: Manifestações clínicas e avaliação auditiva - Martins, Regina Helena Garcia [UNESP]; Nakanishi, M. [UNESP]; Dias, N. H. [UNESP]; Sousa, J. C. [UNESP]; Tamashiro, I. A. [UNESP] (My University, 2001)
Introduction: Children with Moebius syndrome may present paralysis of cranial nerves III, IV, V, VI, VII, VIII, IX, X and XII, compromising motor and sensorial functions. Hands and feet defects (syndactyly, equinovarus and arthrogryposis) are frequently associated. These manifestations can be attributed to the use of misoprostol during pregnancy to induce abortion. Study design: Clinical prospective. Aim: To evaluate the main clinical manifestations, hearing acuity and possible etiologic factors in children with Moebius syndrome. Material and method: The children were submitted to clinical, otolaryngological and hearing acuity assessment. Hearing acuity was evaluated through behavioral tests, pure tone audiometry, tympanometry and auditory brainstem response (ABR). We investigated possible etiologic factors. Results: Three boys and two girls were evaluated. The main manifestations were: facial paralysis, paralysis of masseter muscle, defects in dental occlusion, retraction of tympanic membrane, equinovarus, oblique palpebral fissure and tongue atrophy. Conductive hearing loss was detected in three children and sensorineural hearing loss in one child. The use of misoprostol during pregnancy was reported by four mothers. Conclusions: The children with Moebius syndrome evaluated in the present study manifested palsies of various cranial nerves, especially V, VII and XII nerves, responsible for motor and sensorial alterations. Inadequate eustachian tube function associated to conductive hearing loss was frequent. The use of misoprostol during pregnancy was reported by the mothers and it was considered a possible etiologic factor.
Moebius sequence: Clinical manifestations and hearing assessment
Keywords: ABR; Facial palsy; Hearing loss; Moebius syndrome; Otorhinolaryngology; misoprostol; arthrogryposis; child; conduction deafness; cranial nerve paralysis; eardrum; evoked brain stem auditory response; facial nerve; facial nerve paralysis; foot malformation; hand malformation; hearing acuity; hearing impairment; human; masseter muscle; palpebral fissure anomaly; perception deafness; pes equinovarus; prenatal drug exposure; pure tone audiometry; syndactyly; tongue disease; tooth occlusion; trigeminal nerve; tympanometry; vestibulocochlear nerve